Network protocol identification based on active learning and SVM algorithm - Yi-peng WANG; Xiao-chun YUN; Yong-zheng ZHANG; Shu-hao LI (Tongxin xuebao)
Obtaining qualified training data for protocol identif ion generally requires domain experts to be involved,which is time-consuming and laborious.A novel approach for network protocol identification based on active learning and SVM algorithm was proposed.The experimental evaluations on real-world network traces show this approach can accurately and efficiently classify the target network protocol from mixed Internet traffic,and meanwhile display a sig-nificant reduction in the number of labeled samples.Therefore,this approach can be employed as an auxiliary tool for analyzing unknown protocols in real-world environment.